Accuracy of recall of histories of oral contraceptive use. Issue 4 (November 1974) - Glass, Roger; Johnson, Bridget; Vessey, Martin
Abstract : Published retrospective studies of the relationship between the use of oral contraceptives and disease have assumed that women are able to recall their oral contraceptive histories with reasonable accuracy. The validity of this assumption has been investigated by comparing oral contraceptive histories obtained from 75 women attending family planning clinics with the information contained in the clinic records. It is concluded that simple measures of oral contraceptive use, such as whether the preparations have ever or never been used, whether they are in current use, and the total duration of use, are likely to be remembered with adequate accuracy.